The oneness of the manifold: a comparative survey of mystical ontologies east and west - Klotz, Jerome (2021)
This study consists of a two-part comparative survey of mystical ontologies East and West. Part One examines the Eastern traditions of Advaita Vedānta Hinduism, philosophical Daoism, and Zen Buddhism, while Part Two takes for its focus the Western traditions of Kabbalistic Judaism, mystical Christianity, and mystical Islam. The burden of my thesis is to show how these traditions coalesce around a shared conception of existence as simultaneously one and manifold. According to this shared conception, just as many waves “are” only as the restricted articulations of a single ocean, or just as many rays of light “are” only as the diversified modes of a single sun, so all phenomena “are” only as the discrete manifestations of a single meta-ontological Principle or Field. I survey this point of correspondence under the three interrelated headings of existence, manifestation, and knowledge. In doing so, I hope to demonstrate how the mystical ontologies of the East and the West provide the possibility of a mutual understanding among religions at the ontological level.